2013
DOI: 10.1089/aid.2012.0102
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Antiretroviral Resistance Among HIV Type 1-Positive Prisoners in the Southeast United States

Abstract: Drug-resistant HIV complicates management of HIV infection. Although an estimated 14% of all HIV-positive persons pass through a prison or jail in the United States each year, little is known about the overall prevalence of antiretroviral (ARV) resistance in incarcerated persons. All genotypic sequence data on HIV-positive prisoners in the North Carolina (NC) Department of Corrections (DOC) were obtained from LabCorp. Screening for major resistance mutations in protease (PI) and reverse transcriptase (NRTI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…A large observational study of testing and linkage to care in 10 cities in the United States demonstrated improved HIV treatment outcomes at six-months post release [87]. Evidence on viral resistance to antiretrovirals among incarcerated populations was mixed [100,101], however incarceration was associated with elevated VL and associated risk factors among illicit drug users in Vancouver, Canada [99]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large observational study of testing and linkage to care in 10 cities in the United States demonstrated improved HIV treatment outcomes at six-months post release [87]. Evidence on viral resistance to antiretrovirals among incarcerated populations was mixed [100,101], however incarceration was associated with elevated VL and associated risk factors among illicit drug users in Vancouver, Canada [99]. …”
Section: Resultsmentioning
confidence: 99%
“…A molecular phylogeny inferred from the analysis of viral RNA sequences from 40 individuals did not find any evidence of between-prisoner transmission; however, analysis of sequences from the pol gene evidenced high rates of HIV primary and secondary resistance [100]. In contrast, a survey of 367 viral sequences from individuals incarcerated in the state prison system of North Carolina found moderate levels of drug resistance, comparable to non-incarcerated populations [101]. …”
Section: In-prison Hiv Treatment and Linkage To Post-release Casementioning
confidence: 99%
“…In North America, data were available for pretreatment DRMs from 19,563 individuals with HIV (Supplemental Tables 18 and 19 in Additional file 1) [52,[86][87][88][89][90][91][92][93][94][95][96][97][98][99]; 6% (n=1,062/17,951) and 8% (n=1,413/17,951) had mutations resistant to the NRTI and NNRTI classes, respectively. The most frequent pretreatment 3TC/FTC DRMs were at position M184 (1%; n=216/15,401); the most frequent pretreatment RPV DRMs were at positions E138 (2%; n=5/317) and V179 (1%; n=43/6,380).…”
Section: Regional Prevalence Estimates: North Americamentioning
confidence: 99%
“…The Trugene ® HIV-1 Genotyping Kit (Siemens Healthcare Diagnostics, USA) and the ViroSeq™ HIV-1 Genotyping System (Celera Diagnostics, USA) are both CE-IVD-marked in Europe and approved by the FDA in the USA [61,62]. Many other commercial genotyping assays, such as GenoSure ® MG (Monogram, future science group USA), and less-expensive in-house genotyping assays have also been well evaluated worldwide [63][64][65][66]. The major limitation of both widely validated kits is that they were designed based on the HIV-1 subtype B viral genome, and their performance on HIV-2 or other HIV-1 genotypes remains uncertain.…”
Section: Cd4 + T-lymphocyte Enumerationmentioning
confidence: 99%